Relokasi hiposenter gempabumi Sumatera Barat menggunakan metode double difference (DD) - Anggina Wulan Dari (PILLAR OF PHYSICS, 2016)
West Sumatra is located in an active subduction zone between the Indo-Australian plate with the Eurasian Plate and is along the Sumatra fault, so the West Sumatra earthquake prone. One way to understand the tectonic conditions of this region by relocating the earthquake hypocenter. Earthquake hypocenter result of BMKG has some weaknesses due to the program that used (SeiscomP) has a minimum depth of 10 km (fixed depth).Beside that  velocity model of  P wave  which used by the system does not match with the actual geology condition of Sumatra Barat. The data used for the relocation of the hypocenter are taken for BMKG analysis system SeisComP the until period 1 May 2009 to 30 November 2015 by using HypoDD  program with double difference method in it. AK 135 and Madlazim wave velocity model are used in the program. Double Difference method. So the velocity model errors can be minimized without using correction station. The results indicate earthquake hypocenter relocation in West Sumatra related to the fault, subduction process and Mentawai fault. The data relocation many as 1181 of the 1622 data. Based on the data obtained by percentage depth to a shallow earthquake relocation 79.3%, 45% intermediate earthquake and the earthquake in 0%. This is due to the deeper the layer, the higher the P wave velocity, so that the structure of the constituent layers will be more complex. Besides the depth of the earthquake below 10 km (fixed depth) after relocation has a variety of different depths. Earthquakes before relocating spread out so the (trendline) can not show a pattern corresponding to the main fault. Once relocated the (clusters) to form a group on the trend of the field fracturing or similar structure and distribution of earthquakes portrayed clearly. The RMS value after the relocation ranges between 0-1.5 and the RMS value before relocating ranging between 0-5